1997
DOI: 10.1159/000169069
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ventilatory Responses in Severe Acidemia in Diabetic Ketoacidosis

Abstract: Ventilatory response in patients with severe acidemia in diabetic ketoacidosis (DKA) was unresolved. Thus, 83 patients with uncomplicated DKA were studied for the relation between arterial blood pH, calculated bicarbonate concentration (HCO3) and carbon dioxide tension (PCO2). The equation for the PCO2/HCO3 pair was: PCO2 =1.58 × HCO3 + 7.6 (SE 2.55, r = 0.95, p < 0.01); for the PCO2/pH pair was: PC02 = 43.8 × pH-293 (SE 6.23, r = 0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…To determine the degree of agreement between measured EtCO 2 and vHCO 3 − , we sought to convert the EtCO 2 value into a comparable value. The following formula was published for use in patients with metabolic acidosis and is validated for use in predicting measured arterial HCO 3 − (mmol/L) from arterial pCO 2 (mmHg) (7–9):…”
Section: Methodsmentioning
confidence: 99%
“…To determine the degree of agreement between measured EtCO 2 and vHCO 3 − , we sought to convert the EtCO 2 value into a comparable value. The following formula was published for use in patients with metabolic acidosis and is validated for use in predicting measured arterial HCO 3 − (mmol/L) from arterial pCO 2 (mmHg) (7–9):…”
Section: Methodsmentioning
confidence: 99%
“…1 The normal physiologic compensation for metabolic acidosis is to increase minute ventilation, thereby decreasing arterial carbon dioxide tension (PaCO 2 ). Prior studies [2][3][4] using arterial blood gas analyses have shown that patients with metabolic acidosis demonstrate a predictable decrease in PaCO 2 such that Ϫ PaCO = 1.5 ϫ [HCO ] ϩ 8 2 3 The partial pressure of CO 2 at the end of an exhaled breath (ETCO 2 ) closely approximates arterial CO 2 (PaCO 2 ). 5 This relationship has been confirmed in normal children using nasal capnography.…”
mentioning
confidence: 99%
“…Guh et al have suggested that at lower pH values, the hyperventilatory response is not complete (8). These authors studied 83 adult patients with uncomplicated DKA.…”
Section: Discussionmentioning
confidence: 99%